Contemporary forward gold transactions and their harmonization with views of ibn Taymiyyah and ibn Qayyim al-Jawziyyah: Comex New York gold futures as case study / Moctar Moussa Djibrilla - Moctar Moussa , Djibrilla (2017)
Despite the abolition of the gold monetary system, which was used in prior eras of Islamic civilization, along with the domination of forward products in the contemporary gold business sector, the majority of Muslims jurists still emphasize that to defer delivery of product or delay payments is highly prohibited in gold transactions. This study argues that in the contemporary world, where gold does not play any role as currency, there are credible views based on solid Islamic legal sources from Ibn Taymiyyah and Ibn Qayyim that permit deferred delivery and delayed payment in gold business contracts. However, this is limited to gold matter that isn’t minted by a monetary authority for currency purposes. Thus, the main objective of this study is to discuss the modern forward gold contracts and gold futures and to discover how far these products are in harmony with Ibn Taymiyyah and Ibn Qayyim’s views that permitted defer delivery and delay payment in noncurrency gold transactions. In order to achieve the goals of this study the researcher used the following methods: induction, comparative, and analysis approaches. In addition, a qualitative approach was used in order to conduct interviews to hear the views of fatwa issuers and shari’ah experts in the gold business sector. Moreover, the analysis of secondary data and interview responses indicates that gold and all of its derivatives (ore, coins, dīnār, jewellery, etc.) have been used by Muslims as one of the major currencies during the time of the Prophet (PBUH) and his companions (RDAN). However, it was found the role of gold as currency was confined to the dinar and Muslim scholars were divided in to different views about gold transactions. The majority view, known as the Jumhur, prohibited deferred delivery and delayed payment gold transactions. However, the minority view, held by Ibn Taymiyyah and Ibn Qayyim, permitted it under certain circumstances. This study adopts the minority opinion in accordance with valid Islamic sources and contemporary realities. Finally it was suggested that more research is needed to determine the general prohibitions that Ibn Taymiyyah and Ibn Qayyim’ views did not allow to be applied in modern forward gold transactions and gold futures